A Novel & Unique Framework for Visual Information Analysis in Scientific Scholarly Literature - A. Aruna, S. Guruprasad, A. Koushik Gupta, M.K. Praveen Keshav (International Journal of Advanced Science and Technology, 2020)
Visual analytics is an emerging multidisciplinary research area which can be effectively used in the field of visual information system management. Most of the scientific literature consist of vast alpha-numeric data. Data collection and data management methodology plays a vital role in any scientific visual information system. It is a key requirement to search and find information on the efficiency of the approach. Past few years, scientific research scholarly literature is published at a high frequency. Therefore, it is essential to develop a novel framework to search and navigate the paper to identify various visual elements like plots, photographs, illustrations, diagrams and table. This paper offers us method to strategically retrieve data from such elements using visual information analysis (combination of text-mining and image processing).